The impact of networks, segregation and diversity on migrants' labour market integration - Thomas Horvath; Peter Huber (WWWforEurope, 2013)
We analyse the role of ethnic networks, segregation and diversity of a region on migrants success in integration into the host countries labour markets. We find a robust negative impact of ethnic networks on unemployment probabilities of the foreign born and a positive one on employment probabilities. In addition a similarly robust positive impact of ethnic diversity on the unemployment probabilities and a negative one on employment probabilities is found. With respect to over-education our results are less robust, but in their majority point to a negative impact of ethnic networks on the probability of over-educated employment and an insignificant or positive impact of diversity. Segregation at the country level, by contrast, remains an insignificant determinant of both the probability of unemployment and of overeducated employment in most specifications and all three variables seem to be only very weakly correlated to the probability of being detached from the labour market and to the probability of being in education.
Keywords: D83; J71; R23; 330; Integration; networks; diversity